Coccidioidomicose no Brasil: os desafios de uma doença negligenciada - Moura, Santiago Gonçalves Bezerra (2021)
Coccidioidomycosis is a deep-seated infection caused by two cryptic species of dimorphic fungi: Coccidioides immitis and C. posadasii. In Brazil, the disease occurs exclusively in the Northeastern region, affecting mainly rural populations living in situation of economic and social vulnerability. Epidemiologic aspects of the disease in Brazil are elusive and financial investments in researches seeking new therapeutic options to treat the infection are scarce. Hence, this study has two main objectives: 1) to investigate the antifungal potential of promethazine (PMZ) and cyclosporine A (CSA) against C. posadasii; and 2) to discuss the inclusion of coccidioidomycosis on the World Health Organization’s (WHO) list of Neglected Tropical Disease (NTD). Therefore, susceptibility tests were performed by macrodilution methodology according to the document M38-A2 of the Clinical and Laboratory Standards Institute (CLSI). Minimal inhibitory concentration (MIC) was defined as the lowest concentration able to inhibit 100% of visible fungus growth when compared to the control. Interaction between PMZ and amphotericin B (AMB) or voriconazole was evaluated by checkerboard test. All the experiments were performed in triplicates in a biosafety cabinet class II, in a biosafety level 3 laboratory. The results obtained show that PMZ and CSA were able to inhibit C. posadasii growth, with MICs raging from 16 to 64 µg/ml and from 1,56 to 12 µg/ml, respectively. Besides, synergic interaction between PMZ and VRZ was observed, reducing the antifungal concentration necessary for inhibition of 100% of visible fungal growth of AMB and VRZ in 88% and 94%, respectively. However, more studies must be performed in order to understand the mechanisms involved in the inhibitory activity observed. Besides, a systematic review about coccidioidomycosis cases in Brazil was conducted. Based on the regions where the cases were reported, sociodemographic data about the populations affected by the disease were raised. As result, the raised data showed the social and economic vulnerability situation faced by populations affected by the disease in Brazil. In this context, we believe that the inclusion of coccidioidomycosis on the NTD list would enable implementation of an epidemiological surveillance system to support the development of prophylactic and educational measures to the most vulnerable population.